Analisis Pengaruh Kepemimpinan Transformasional dan Motivasi Terhadap Kualitas Kehidupan pada Bank Syariah PT.BPRS Puduarta Insani - Novita Ayunda Sari; Nurul Jannah (Universitas Muhammadiyah Enrekang, 2022)
The success of a company is strongly influenced by the performance of its employees. It is certain that the company will always try to improve employee performance. The purpose of this study was to determine whether the Transformational Leadership Style and Work Motivation had a significant effect on the Quality of Life at BPRS Puduarta Insani Medan. The sampling technique in this study was saturated sampling, which took the entire sample of 18 respondents. The research method is the associative method, the analysis technique used is multiple regression. The results showed that Transformational Leadership Style and Work Motivation simultaneously had a significant effect on Quality of Life. Partially, only work involvement has a significant effect on employee performance. The leadership of BPRS Puduarta Insani Medan should be able to pay attention to work involvement that can improve employee performance so that the targets set can be achieved.